Investigation on seismic performance and functionality of self-centring post-tensioned segmental columns - Nikbakht, E. (Taylor and Francis Ltd., 2018)
The precast post-tensioned segmental columns react against lateral seismic loading with low residual displacement, predominantly because of the self-centring capability of post-tensioning strands. However, their application is still limited in high seismic zones due to their unknown behaviour during and following severe earthquake loading. In this work, experimental study is conducted to inspect the functionality of post-tensioned segmental columns after suffering severe damages. In earlier work by the authors, partial yield of central strands had been occurred during the unloading stage in the last cycle at 4 drift level. In current study, the experimental work is extended and the specimen retested under loading and unloading up to 4.0 drift. The results indicate that the first segment shows approximately 10Â mm horizontal movement on the surface of foundation. However, the specimen showed identical strength at 4.0 drift level. In addition, using finite element method (FEM), a numerical study was conducted in order to investigate the influence of various parameters such as mild steel ratio, concrete strength, number of segments, post-tensioning force and axial loading. Finally, design recommendations were proposed for the yield displacement, ductility and correlation of residual displacement and displacement ductility of post-tensioned segmental columns with various aspect ratios. Â© 2017 Informa UK Limited, trading as Taylor & Francis Group.